Effect of Some Aromatic Plants on The Life of Mosquito Larvae and Virgins and Their Possible Use In Biological Control - Khadir Al-Rashidi, Ghazwane Thamer; Ali, Abeer Isameel (Nabatia, 2025)
Contemporary control tactics emphasize the biological management of immature mosquito stages. It was observed that a seedling weighing 10 g in 100 cm of water containing Origanum vulgare and 30 larvae of Culex pipiens molestus accelerated their life cycle duration from 14 days in the control group to 11 days in the experimental group, alongside an 80% apparent reduction in larvae of C. pipiens molestus. The efficacy diminished to 50% and 30% at 200 cm and 300 cm, respectively, with stable plant weight. At start, there was a distinct distortion of the complement; Mint of the species Mentha pulegium has a lethal impact of 50% on mosquito larvae with individual seedlings. The constant weight in 100 cm of water was reduced to 35%, while an increase of 20% in water amount was seen at 200 cm and 300 cm, respectively, with stable plant weight. Additionally, this resulted in deformities in the remaining buds (inability to fly) by 18% ± 5%. The mint plant had no impact on the life cycle of mosquitoes.